Selective electrochemical glycosylation by reactivity tuning. - France, R; Compton, R; Davis, B; Fairbanks, A; Rees, N; Wadhawan, J (2004)
Electrochemical glycosylation of a selenoglycoside donor proceeds efficiently in an undivided cell in acetonitrile to yield beta-glycosides. Measurement of cyclic voltammograms for a selection of seleno-, thio-, and O-glycosides indicates the dependence of oxidation potential on the anomeric substituent allowing the possibility for the rapid construction of oligosaccharides by selective electrochemical activation utilising variable cell potentials in combination with reactivity tuning of the glycosyl donor. A variety of disaccharides are readily synthesised in high yield, but limitations of the use of selenoglycosides as glycosyl donors for selective glycosylation of thioglycoside acceptors are exposed. The first electrochemical trisaccharide synthesis is described.